Inhibition of topoisomerase IIα: novel function of wedelolactone - Benes, Petr; Knopfova, Lucia; Trcka, Filip; Nemajerova, Alice; Pinheiro, Diana; Soucek, Karel; Fojta, Miroslav; Smarda, Jan (Cancer letters, 2011)
The naturally occurring coumestan wedelolactone has been previously shown to reduce growth of various cancer cells. So far, the growth-suppressing effect of wedelolactone has been attributed to the inhibition of the NFκB transcription factor and/or androgen receptors. We found that wedelolactone suppressed growth and induced apoptosis of androgen receptor-negative MDA-MB-231 breast cancer cells at concentrations that did not inhibit the NFκB activity. The cells responded to wedelolactone by the S and G2/M phase cell cycle arrest and induction of the DNA damage signaling. Wedelolactone interacted with dsDNA and inhibited the activity of DNA topoisomerase IIα. We conclude that wedelolactone can act as growth suppressor independently of NFκB and androgen receptors.
Keywords: DNA vazebné proteiny; Topoisomerase Inhibitors; Enzyme-Linked Immunosorbent Assay; nádory prsu; apoptóza; DNA Damage; Female; DNA-topoisomerasy typu II; Cell Line, Tumor; Antigens, Neoplasm; ženské pohlaví; Apoptosis; Cell Cycle; lidé; Antineoplastic Agents; protinádorové látky; Coumarins; Breast Neoplasms; signální transdukce; Signal Transduction; Immunoblotting; buněčný cyklus; kumariny; poškození DNA; ELISA; inhibitory topoisomeras; Cell Growth Processes; DNA Topoisomerases, Type II; DNA-Binding Proteins; buňky - růstové procesy; imunoblotting; Cell Survival; viabilita buněk; antigeny nádorové; nádorové buněčné linie; Humans